Physical activity partially mediating the social gradient in adolescent mental health - Dahlstrand, Johan; Lin, Qinyun; Friberg, Peter; Fridolfsson, Jonatan; Chen, Yun (Frontiers in Public Health, 2025)
ObjectivesTo examine whether there is a socioeconomic status (SES) gradient in adolescent mental health problems, and if so, whether out-of-school physical activity mediates this gradient.MethodsBased on data from 1,285 adolescents in Sweden, we used linear regression analysis to examine whether the social gradient in mental health problems (stress and psychosomatic symptoms by survey) varied by SES indicators, including income, father’s and mother’s education (register data). Parameter estimates were obtained using ordinary least squares. We also investigated if out-of-school physical activity (accelerometer data) mediates these gradients by applying the potential outcomes framework for mediation analysis. This framework accounts for potential exposure-mediator interaction, and confidence intervals were calculated using bootstrapping.ResultsGradients in adolescents’ mental health problems were observed for all SES indicators, the coefficient of determination R2 showing the different SES indicators explained between 0.7–1.4% of stress and 0.5–1.2% of psychosomatic symptoms. Out-of-school vigorous-physical-activity (VPA) and moderate-to-vigorous-physical-activity (MVPA) partially mediated the gradients related to income in the overall sample. Specifically, VPA mediated 6.8% of the association between income and stress, and 9.2% of the association between income and psychosomatic symptoms, while MVPA mediated 5.4 and 6.6% of these associations, respectively. Regarding father’s education, VPA mediated 15.7% of the association with stress and 10.2% with psychosomatic symptoms, whereas MVPA mediated 14.6 and 8.9%, respectively. Sex-stratified analyses revealed that these mediation effects were statistically significant only among females. For mother’s education, mediation effects were observed exclusively in the female subgroup. VPA mediated 24.1% of the association with stress and 24.0% with psychosomatic symptoms, while MVPA mediated 20.8 and 21.5% of these associations, respectively.ConclusionThere are social gradients in adolescents’ mental health problems based on income and parents’ education, and these gradients appear to be partially mediated via out-of-school VPA and MVPA, predominantly among females.